How women won the vote : Alice Paul, Lucy Burns, and their big idea - Bartoletti, Susan Campbell (Harper, 2020)
Presents a picture book history of the key events and women that contributed to the first women's march in 1913, and the passage of the 19th Amendment. Discusses how American suffragists Alice Paul and Lucy Burns met in a London prison while fighting for votes for women, and forged an eleven-year alliance that culminated in the march and eventually secured women's right to vote in 1920. Includes archival photographs, memorabilia from the suffrage era, a timeline, and further reading.